Assessment of the link between in utero exposure to 2-aminoanthracene (2AA) and type-1 diabetes (T1D). Issue 1 (December 2017) - Mays, Christopher; Hunter, Daniel; Yau, Wilson; Gato, Worlanyo
Abstract Background A recent diabetes report revealed an increased incidence in diabetes including type 1-diabetes (T1D). The increase in the numbers of T1D incidences are thought to be related to environmental reasons such as the exposure to environmental chemicals including arylamine 2-aminoanthracene (2AA). T1D is an autoimmune disease of the pancreatic islet in which insulin-producing beta cells are destroyed by auto-reactive T-cells and monocytic cells. Methods The purpose of this study is to examine the extent to which 2AA exposure contributes to T1D. Three groups of pregnant Sprague Dawley dams ingested various concentrations of dietary 2AA from gestation through the postnatal period. A select number of cytokines and adipokines previously noted to play a significant role in inflammatory response were analyzed in the pancreas of the pups for alteration. The anatomy of the pancreas was also evaluated to determine any histological changes. Results Results showed over-expression of pro-inflammatory protein IL-6. Up-regulation of humoral genes IL-7 and IL-21 were also noted. Pathologic characterization showed no significant changes. Moreover, serum total protein was significantly reduced in exposed groups. Elevated serum glucose concentration seems to correspond to slightly lower insulin levels in serum. Cumulative neonatal weight gain analysis showed no major alterations between the control and gestationally-exposed rats. Conclusion It appears that systemic effects of 2AA ingestion were mild in the neonates. Further assessments of pups who lived longer than two weeks could be a useful way to measure the progression and possibly further support our hypothesis that 2AA can lead to systemic effects that are indicative of inducing T1D.